Reflective practice via the lens of the life career and paradox: a contemplation of being and becoming a social worker. Issue 2 (3rd March 2020) - Gee, Ricky; Barnard, Adam
ABSTRACT: Reflective practice constitutes an important aspect of social work enactment, with a range of theory available to the practitioner. This paper continues this heritage with a theory of reflection informed via continental philosophy. The theory advocated here considers the life career of the practitioner via the duality of being and becoming, providing a critical lens upon retrospective enactment illuminating paradoxical moments. Such moments provide diachronic and nuanced insights into enactment across a range of interconnected strands of the life career, allowing the practitioner to consider important emergent themes across career articulation and thus action within and outside the vista of paid employment. This paper provides a case illustration to demonstrate the penetrative nature of such a lens, advocating future research endeavours to inform social work pedagogy and practice.